Research on regression test method based on multiple UML graphic models. (4th June 2020) - Qu, Mingcheng; Wu, Xianghu; Tao, Yongchao; Wang, Guannan; Dong, Ziyu
Most of the existing graph-based regression testing schemes aim at a given Unified Modelling Language (UML) graph and are not flexible in regression testing. This paper proposes a method of a universal UML for a variety of graphical model modifications, and obtains a UML graphics module structure modified regression testing must be retested, determined by the domain of influence analysis on the effect of UML modification on the graphical model test case generated range analysis, finally re-auto generate test cases. This method has been proved to have a high logical coverage rate. In order to fully consider all kinds of dependencies, it cannot limit the type modification of UML graphics, and has higher openness and comprehensiveness.